Validation of an online questionnaire for identifying people at risk of familial and hereditary colorectal cancer - Kallenberg, F. G. J. (Fam Cancer, 2015)
We developed and validated an online questionnaire to document familial cancer history, in order to facilitate the detection of persons with a familial or hereditary colorectal cancer (CRC) risk. The development of the self-administered online questionnaire for the assessment of familial and hereditary CRC risk was based on nationwide criteria for referral to genetic specialists due to a Lynch syndrome suspicion, as well as existing criteria for surveillance colonoscopies because of an increased risk of familial CRC. The questionnaire was validated at a private colonoscopy center. Patients scheduled for colonoscopy were enrolled (n = 150). Performance of the questionnaire was assessed by comparing referrals based on questionnaire data against referral decisions based on full pedigree data. In a second validation phase, referrals based on questionnaire data were compared with referrals based on data collected in a telephone interview. We also calculated inter-observer agreement in referral decisions. In the first validation phase, the questionnaire had a sensitivity of 90 % (95 % CI 55–98 %) at a specificity of 98 % (95 % CI 87–100 %) in identifying persons qualifying for referral. In the second validation phase, sensitivity was 100 % (95 % CI 63–100) at a specificity of 97 % (95 % CI 91–99 %). In both validation phases an inter-observer agreement of 100 % in referral decisions was achieved. The online questionnaire has a high sensitivity and specificity in identifying persons qualifying for referral because of suspected Lynch syndrome or familial CRC. Implementation of this tool in colonoscopy clinics can facilitate the detection of patients with hereditary or familial CRC.